PUTUSAN MAHKAMAH KONSTITUSI BERSIFAT FINAL DAN MENGIKAT (BINDING) - Johansyah, Johansyah (Faculty of Law, University of Palembang, 2021)
The Constitutional Court has the authority to judge at the first and last levels whose decisions are final and binding. The Constitutional Court decision which is final and binding, contains 4 (four) legal meanings, namely: First, in order to realize legal certainty as soon as possible for the disputing parties. Second, the existence of the Constitutional Court as a constitutional court. Third, meaning as a form of social control exercised by the Constitutional Court. Fourth, as the guardian and sole interpreter of the constitution. The Constitutional Court's decision is final and binding, giving birth to a number of legal consequences in its application. Constitutional Court decisions can be classified into 2 (two) broad lines, namely decisions of the Constitutional Court which have positive legal consequences and negative legal consequences. As for the legal consequences that have positive meanings, namely: Ending a legal dispute; Maintain the principle of checks and balances; and Encouraging the political process. Meanwhile, the legal consequences arising from the Constitutional Court's decision are final and binding in a negative meaning, namely: The closure of access to legal remedies and the occurrence of legal vacuum.